2019
DOI: 10.1007/s13187-019-01549-8
|View full text |Cite
|
Sign up to set email alerts
|

Project ECHO: a Potential Best-Practice Tool for Training Healthcare Providers in Oral Cancer Screening and Tobacco Cessation

Abstract: The oral cancer pandemic and inadvertent tobacco consumption have rendered timely oral cavity screening and tobacco cessation essential, skills which most healthcare providers (HCPs) lack. Project BExtension for Community Healthcare Outcomes( ECHO) is a proven best-practice tool for virtual telementoring of primary care providers by experts at academic health centers, in managing complex medical conditions in rural, expert-deficient setups. For the first time, our organization in India has utilized this method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 10 publications
2
18
0
3
Order By: Relevance
“…These ndings are similar to improvements reported among dentists and gynecologists undergoing similar training. (14,15) The study, however, shows no statistical difference in primary care physicians' implementation of cancer screening services in their healthcare organizations, at the end of the 3-month training compared to when they enrolled in the program. This highlights a critical gap in promoting cancer prevention objectives in India and indicates the need for further research to explore the barriers to implementation of cancer screening services in the national and the regional and/or local context.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…These ndings are similar to improvements reported among dentists and gynecologists undergoing similar training. (14,15) The study, however, shows no statistical difference in primary care physicians' implementation of cancer screening services in their healthcare organizations, at the end of the 3-month training compared to when they enrolled in the program. This highlights a critical gap in promoting cancer prevention objectives in India and indicates the need for further research to explore the barriers to implementation of cancer screening services in the national and the regional and/or local context.…”
Section: Discussionmentioning
confidence: 79%
“…The ECHO model is well suited to the Indian context in that it offers a virtual platform, is cost effective, and provides the ability to train physicians over a wide geographical spread in a limited time period. Globally, ECHO programs have shown evidence in improving provider knowledge and skills for treatment for several medical conditions such as Hepatitis C (12), Multiple Sclerosis (13), and behavioral disorders (14). Despite the growing number of studies evaluating ECHO, a recent systematic review by McBain and colleagues concluded that the evidence of effectiveness was modest compared to the widespread implementation of the model internationally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…El cáncer, en cualquiera de sus variantes y localizaciones, constituye un problema de salud para el hombre moderno (Laslo & Lehmann, 2019;Nethan et al, 2019), sobre todo porque es una enfermedad crónica que se incrementa de manera proporcional al envejecimiento de la población (Cruz et al, 2016;Peña et al, 2016;Nagao & Warnakulasuriya, 2020). No obstante, la existencia de factores relacionados con el estilo de vida, tales como los hábitos tóxicos, la dieta y la exposición a diversos agentes exógenos, afectan de forma negativa los índices de morbilidad y mortalidad de las enfermedades crónicas como las neoplasias (Cruz et al, 2016;Shao et al, 2019;Nethan et al, 2019;Deluche et al, 2020). Esto ha contribuido a que la incidencia de tumores malignos haya aumentado en Cuba, a tal punto, que en muchas provincias el cáncer constituye la segunda causa de muerte, solo precedido por las enfermedades cardiovasculares (Ford & Farah, 2013;AES, 2017;Nethan et al, 2019),y la primera en incidir en años potenciales de vida perdidos.…”
Section: Introducción 186unclassified
“…No obstante, la existencia de factores relacionados con el estilo de vida, tales como los hábitos tóxicos, la dieta y la exposición a diversos agentes exógenos, afectan de forma negativa los índices de morbilidad y mortalidad de las enfermedades crónicas como las neoplasias (Cruz et al, 2016;Shao et al, 2019;Nethan et al, 2019;Deluche et al, 2020). Esto ha contribuido a que la incidencia de tumores malignos haya aumentado en Cuba, a tal punto, que en muchas provincias el cáncer constituye la segunda causa de muerte, solo precedido por las enfermedades cardiovasculares (Ford & Farah, 2013;AES, 2017;Nethan et al, 2019),y la primera en incidir en años potenciales de vida perdidos. Por eso constituye en el presente, la causa de mayor impacto en la esperanza de vida al nacer (Miranda, 2014;Padilla et al, 2016;Shao et al, 2019;Deluche et al, 2020).…”
Section: Introducción 186unclassified